Awareness and Satisfaction of Employees on the Corporate Social Respon-sibility Services in Hanjin Heavy Industries and Construction Philippines - Rosa, Honeylyn R. Dela (Future Science / FSH-PH Publications, 2024)
Hanjin Heavy Industries Construction Philippines Inc. offers CSR services to motivate employees and ensure security. Employees receive free shuttle buses, food allowances, medical and dental missions, schools, and housing loans. However, the infrequent utilization of these services could potentially impact job performance. Employee satisfaction with these services may influence their satisfaction, leading to lower working conditions. This study aimed to assess employee awareness and satisfaction with Hanjin social responsibility services in 2019. The research involved 11 employees (85) and 25 department managers from the Hanjin Subic Shipyard. The study used questionnaires to gather data on employees' profiles and awareness of the company's benefits. The results were analyzed using descriptive statistical tools and gathered through a pilot data-gathering process. The survey shows that all respondents benefit from the company's annual physical examinations, which are both the company's and employees' responsibility. The services include free shuttles, food allowances, medical and dental assistance, housing, and educational assistance. Basic occupational safety and health training was taken by 41.82 percent of respondents. Management training and development was received by 0.91% of employees. Higher awareness contributes to employee satisfaction with Hanjin CSR services. The management of Hanjin raises employee awareness of CSR services by holding a symposium and disseminating various information, for example.